Peningkatan kinerja pompa hidram berdasarkan posisi tabung kompresor dengan saluran keluar di bawah tabung kompresor - Susana, I Gede Bawa; Sutanto, Rudy (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2016)
Hydraulic ram pump is operated without fuel and only rely on the height difference of the water source. tube compressor serves to continue the flow of water and increase the pressure in the hydraulic ram pump. To improve the performance of the hydraulic ram pump, experiment with variable position of the tube compressor has been done. The tube compressor is placed on the side of the valve after intake and waste, as well as with an outlet at the bottom of the tube compressor. The experiments were performed on the flow of water from a height of 2.1 m, 2.6 m, 3.1 m, 3.6 m and 4.1 m. The test results showed that the position of the tube compressor affect the performance of the hydraulic ram pump. Tube compressor is placed after the input side and the waste valve has a value greater than the tube compressor that is placed between the input and exhaust valves. The volumetric flow rate output, maximum head, suction force, and the largest thrust force obtained at a height of 4.1 m with the results of each 0.121 l / sec; 16 m; 156.499 N; and 89.48 N. While the largest pump efficiency obtained at a height of 3.1 m waterfall which is 2.618%.